Answers

2014-10-13T14:50:04+08:00
In finding the nth term of a geometric progression you'll have the formula:
a_n = a_!  r^{n-1}
where an is the nth term
         a1 is the first term
         n is the number of terms 
         r is the common ratio
for that particular problem, you have the given as:
an (a5) = 12
a1 = 3
n =  5
finding r you'll have:
a_6 = a_1  r^{5-1}
12 = 3 r^4
r^4 = 4
r =  \sqrt{2}
getting the 2nd, 3rd and 4th terms you'll have:
a_2 = 3( \sqrt{2})
a_2 = 3 \sqrt{2}
a_3 = 3 \sqrt{2} ( \sqrt{2})
a_3 = 6
a_4 = 6 ( \sqrt{2})
a_4 = 6 \sqrt{2}

therefore you'll have the geometric series as:
3, 3√2, 6, 6√2, 12
0